Stoicism and the Value of Life - Gregory Ponthiere (Global Labor Organization (GLO), 2024)
Although the attitude towards death was central to Stoic philosophy, economists studying the value of life paid little attention to Stoicism. The goal of this paper is to build an analytical bridge between Stoicism and the economic study of the value of life. We use writings of Epictetus, Seneca and Marcus Aurelius to show that the Stoic thesis of the neutrality of death - one should not be afraid of death, because death causes no harm - is rooted in the Stoic discipline of judgements (one should distinguish things that belong to the self from things that are out of control, such as the duration of life) and in the Stoic discipline of desires (i.e., wish for nothing that is not under one's control). The Stoic thesis of the neutrality of death is formalized by using the Stoic discipline of desires, which is modeled as an extension of the symmetric factor of the preference relation beyond its boundaries under standard preferences. It is shown that, depending on the extension of the indifference relation required by Stoicism, a longer life has either a purely instrumental value, or no value at all.
Keywords: I31; J17; B11; 330; value of life; Stoicism; evil of death; indifference; discipline of desires